2006
DOI: 10.1007/bf03344146
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal hemorrhage due to bilateral adrenal metastases from lung adenocarcinoma

Abstract: A 56-yr-old man was admitted to our university hospital for severe back pain one month after a resection for lung adenocarcinoma (stage IIIA) without evidence of the adrenal mass. Computed tomography (CT) of the abdomen showed bilateral bleeding of adrenal tumors. Endocrinological laboratory studies showed high plasma ACTH and normal serum cortisol levels with the loss of circadian rhythm. Although plasma ACTH levels increased, there was no cortisol response to administration of human corticotropichormone (hCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…We found 19 reports involving 25 patients in the English literature [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The most frequent site of primary tumors resulting in hemorrhagic adrenal metastases is the lung [26,[29][30][31][32][33][34][35][36][37][38][39][42][43][44]. Other primary malignancies include two cases of hepatocellular carcinoma, one case of hepatic angiosarcoma, one case of hepatic hemangioendotheliosarcoma, and two cases of melanoma [27,28,31,40,41].…”
Section: Hemorrhagic Adrenal Massesmentioning
confidence: 99%
“…We found 19 reports involving 25 patients in the English literature [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The most frequent site of primary tumors resulting in hemorrhagic adrenal metastases is the lung [26,[29][30][31][32][33][34][35][36][37][38][39][42][43][44]. Other primary malignancies include two cases of hepatocellular carcinoma, one case of hepatic angiosarcoma, one case of hepatic hemangioendotheliosarcoma, and two cases of melanoma [27,28,31,40,41].…”
Section: Hemorrhagic Adrenal Massesmentioning
confidence: 99%
“…Lam et al reported that only three of 421(0.7%) cases with metastasis adrenal tumors by carcinomas had clinical findings and endocrinological evidence of Addisonʼs disease by metastasis of lung adenocarcinoma [4]. In the reports of 22 cases which were able to evaluate clinical characteristics and outcome in the English and Japanese literature search which we performed since 1980 [8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 19 cases had adrenal insufficiency associated with NSCLC (the pathological type of lung cancer was unknown in one case) and most of them were adenocarcinoma (Table 2). On the other hand, only two cases of adrenal insufficiency associated with SCLC have been previously reported; one was diagnosed by a low serum cortisol level (≦ 2.5 µg/dl) with an elevation of ACTH (241 pg/ml) [23], while the other was diagnosed by a low serum cortisol level (3.0 µg/ml) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral adrenal hemorrhage occurs in 2% of patients with penetrating trauma (1), whereas right adrenal hemorrhage is reported in 2% of liver transplant patients. Hemorrhagic tumor infarction due to primary or metastatic tumors can cause unilateral adrenal hemorrhage (3,6). Isolated case reports in association with long term non-steroidal anti-inflammatory drug use in uncomplicated pregnancy and neurofibromatosis have been reported.…”
Section: Discussionmentioning
confidence: 99%